CRISIS OF PROFESSIONAL STUDYING AS A BACKRGROUND OF STUDENTS' EMOTIONAL BURNOUT - O. Serhieienkova; O. Stoliarchuk (Borys Grinchenko Kyiv Metropolitan University, 2017)
The characteristic of students' emotional burnout as a negative phenomenon of their personal development is presented in the study. The timeliness of studying the psychological peculiarities of students' emotional burnout is determined by the needs of development of preventive measures and correction of such a phenomenon which considerably complicates professional formation of a personality on the stage of its professional studying. Factors, symptoms and typical dynamic of students' emotional burnout are detached. It is identified that its most typical components are emotional emaciation, cynical attitude to studying and future professional activities along with the depreciation of educational achievements. On the ground of analysis of students' interviewing content it is proved the relation between the crisis of professional studying and emotional burnout. It is found out that common crisis of professional studying for certain students may be transformed into the syndrome of emotional burnout as the confluence of the effects of external factors of studying complicacy and internal sensitive characteristics of its subjects. It is established that the most dangerous consequences of emotional burnout on a ground of studying motivation impoverishment and decline of student's academic achievements are depreciation of his educational and professional achievements and disappointment in himself, decrease of working capacity and living tonus, depressive feelings. As typical means of students' emotional burnout preventive measures it was proposed the usage of possessive behavior during the crisis of professional studying, concordance of life and profession oriented values, academic and professional self-esteem harmonization, ambitions level, right organization of rest and leisure time.